Institutions for Regulatory Governance - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
This paper looks at the role and design of regulatory reform institutions in developing countries. These institutions are classified into four broad types: 1) regulatory reform units, commonly known in Organization for Economic Cooperation and Development (OECD) countries as oversight bodies for regulatory reform; 2) high-level committees for regulatory reform, established in some countries to leverage support and take decisions at a high political level; 3) advisory and/or advocacy bodies in charge of proposing improvements to the regulatory system by strengthening coordination and consultation mechanisms and by promoting the regulatory reform agenda; and 4) Ad hoc institutions for regulatory reform, established to launch regulatory reform efforts and to work on a single defined task or activity. This paper is divided into the following sections: section one briefly reviews the theoretical debate and literature about the role of institutions in facilitating higher economic growth, focusing in particular on regulatory institutions and their relevance in developing countries; section two discusses the main features of regulatory reform institutions at the center of government, namely regulatory oversight bodies, high level committees, advocacy and/ or advisory bodies and ad-hoc institutions for regulatory reform; and section three identifies the features of these institutions that are considered to be best practice. Section three also identifies and discusses lessons learned and the implications for establishing and operating such institutions in developing country contexts.